2018
DOI: 10.1111/bpa.12600
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes, an active player in Aicardi–Goutières syndrome

Abstract: Aicardi-Goutières syndrome (AGS) is an early-onset, autoimmune and genetically heterogeneous disorder with severe neurologic injury. Molecular studies have established that autosomal recessive mutations in one of the following genes are causative: TREX1, RNASEH2A, RNASEH2B, RNASEH2C, SAMHD1, ADAR1 and IFIH1/MDA5. The phenotypic presentation and pathophysiology of AGS is associated with over-production of the cytokine Interferon-alpha (IFN-α) and its downstream signaling, characterized as type I interferonopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 78 publications
(124 reference statements)
1
29
0
Order By: Relevance
“…Thus, we tested VAL in an A549 ADAR1-knockout or -knockdown cellular background and observed that VAL selectively inhibited RNase L to suppress cell death. By demonstrating that inhibiting RNase L ribonuclease activity can attenuate ADAR1-associated apoptosis, these results indicate that RNase L is a viable therapeutic target in the context of select cases of AGS with ADAR1 mutations (53). Furthermore, because VAL inhibits RNase L, it is reasonable to expect that, during viral infections, VAL treatment will result in fewer RNA cleavage products to stimulate RIG-I/MDA5 and NLRP3 (25,54).…”
Section: Discussionmentioning
confidence: 84%
“…Thus, we tested VAL in an A549 ADAR1-knockout or -knockdown cellular background and observed that VAL selectively inhibited RNase L to suppress cell death. By demonstrating that inhibiting RNase L ribonuclease activity can attenuate ADAR1-associated apoptosis, these results indicate that RNase L is a viable therapeutic target in the context of select cases of AGS with ADAR1 mutations (53). Furthermore, because VAL inhibits RNase L, it is reasonable to expect that, during viral infections, VAL treatment will result in fewer RNA cleavage products to stimulate RIG-I/MDA5 and NLRP3 (25,54).…”
Section: Discussionmentioning
confidence: 84%
“…In this study, no febrile-related seizures were noted. Hence phenotypic diversity needs to be considered 18, 19, 20, 21. It is worth noting that one of the children with the nodular sclerosis-related gene TSC2 had no seizures after discharge and no signs of nodular sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Four additional genes have been added to the list of AGS causative genes, including RNASEH2C, SAMHD1, ADAR1, and IFIH1/MDA5 (Livingston et al, 2013). Sase et al (2018) overviewed the cellular pathways leading to the AGS phenotype and concluded that the underlying pathophysiological mechanism concerns increased production and dysregulated control of IFNα levels by activation of the cyclic GMP-AMP synthase (cGAS)/stimulator of interferon genes (STING) pathway (Sase et al, 2018). As astrocytes are a major source of IFNα production, this condition is now considered an astrocytopathy (van der Knaap and Bugiani, 2017).…”
Section: Neuropathology Of Aicardi-goutières Syndromementioning
confidence: 99%